Pedagogical evidence of gamification: self-construction and ethnocultural learning of mathematics - Holguin-Alvarez, Jhon (2019)
The studies of gamification in education have increased due to the difficulty of the teaching staff to tackle rigid learning. In this sense, mathematics is complex for didactics in schooling. Therefore, this research describes two quantitative studies, with experimental design. The purpose was to determine the effects of two types of gamification: a) selfconstructive and b) ethnocultural, in the variables learning of addition and subtraction and problem solving respectively. We included 80 fourth grade students in experiment A (M = 10.3 years old, SD = 1.54), and in experiment B we induced 36 first grade students (M = 6.4 years old, SD = 1.36).  We used two instruments: Problem Solving Test and Measurement Test for Learning Addition and Subtraction. From experiment A, we concluded that, ethnocultural techniques developed the resolution of problems with significant effects in the experimental group, the subjects of this experiment developed problems of comparison and equalization with better statistical indicators. Experiment B concluded that the effects were positive in the learning of addition and subtraction operations; with more benefits for the algorithmic and symbolic representation.